Thunderstorm forecast technique for Noi Bai Airport - Trần, Tân Tiến (Đại học Quốc gia Hà Nội, 2014)
This study briefly summarizes the thunderstorm activities in Vietnam. To predict thunderstorms in the Noi Bai Airport region, the thunderstorm indices are calculated for 64 grid points nearby Noi Bai region from the predicted meteorological fields with RAMS (Regional Atmospheric Modeling System) model. The forecast procedure for thunderstorm is built for this region with four prediction factors, such as CAPEmax, Kimax, SI min, Vtmax in the forecast threshold of 0.6. As a result, the occurrence of thunderstorms reaches 80% for the duration of 36 hours. The procedures may be used in the operational prediction.